PENGARUH INSTITUTIONAL OWNERSHIP TERHADAP FINANCIAL PERFORMANCE MELALUI INTELLECTUAL CAPITAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN RETAIL DAN JASA DI INDONESIA - Yoselinda Avelia; Josua Tarigan (Business Accounting Review, 2017)
This study aimed to know the influence of institutional ownership on financial performance, This influenceof the intellectual capital on financial performance, institutional ownership on intellectual capital. Financial performance measured by ROA, ROE, and Tobin’s Q, and Intellectual capital measured by VAIC (Value Added Intellectual Capital Coefficients). The sample consisted of 64 retail and service companies listed on BEI during the period of 2011- 2015. The data collected from annual reports, then analyzed by using WarpPLS version 5.0 software.The result showed that institutional ownership in company gave positive influance to intellectual capital. Intellectual capital was an important asset for company to increase financial performance. Institutional ownership was able to monitor the decision of manager sowas able to increase financial performance. This study has limitation sampel only on retail and service companies.